2015
DOI: 10.14503/thij-13-4059
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Renal Allograft Function via Reduced-Contrast Percutaneous Revascularization of Transplant Renal Artery Stenosis

Abstract: Transplant renal artery stenosis (TRAS),R enal transplantation is the definitive therapy for end-stage kidney disease and provides substantial lifesaving and quality-of-life benefits for patients who would otherwise undergo dialysis.1 Posttransplantation stenosis of the renal artery-more commonly called TRAS, or transplant renal artery stenosis-is the most frequent vascular complication of kidney transplantation.2 It is implicated in graft dysfunction, concomitant congestive heart failure, and refractory hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Unlike the controversial outcomes with renal artery stenosis in nontransplantation patients, improvements in estimated glomerular filtration rate (eGFR) have been reported between 30 and 80 mL/min/1.73 m 2 when transplant perfusion is restored in TRAS and CIAS, 3,4 and there are rare instances of recovery off dialysis. 5 Our patient's kidney function began improving immediately following angioplasty, and 1 week later, she discontinued hemodialysis after a total of 28 days. Her serum creatinine concentration…”
Section: What Would Be the Prognosis For Kidney Transplant Recovery?mentioning
confidence: 69%
“…Unlike the controversial outcomes with renal artery stenosis in nontransplantation patients, improvements in estimated glomerular filtration rate (eGFR) have been reported between 30 and 80 mL/min/1.73 m 2 when transplant perfusion is restored in TRAS and CIAS, 3,4 and there are rare instances of recovery off dialysis. 5 Our patient's kidney function began improving immediately following angioplasty, and 1 week later, she discontinued hemodialysis after a total of 28 days. Her serum creatinine concentration…”
Section: What Would Be the Prognosis For Kidney Transplant Recovery?mentioning
confidence: 69%
“…Post-intervention IVUS helped us to achieve optimal results of all the intervened arterial segments, as reported by other authors, especially for native RAS. 15,16 There are only few published case reports about the use of IVUS in TRAS, [17][18][19] and none for the complex bifurcation lesion as was studied in the index case. Touma et al in a series of 17 patients with TRAS reported higher freedom from intervention and stenosis-free patency with stenting compared to balloon angioplasty (88.2% vs. 76.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Second, PAD may lead to transplant renal artery stenosis and resultant hypertension and progressive renal failure. 7 While rare, this association can lead to graft failure but can easily be mitigated with endovascular therapy. 7 Third, PAD can result in claudication but more importantly can progress to critical limb ischemia (CLI).…”
mentioning
confidence: 99%
“…7 While rare, this association can lead to graft failure but can easily be mitigated with endovascular therapy. 7 Third, PAD can result in claudication but more importantly can progress to critical limb ischemia (CLI). The latter, when present with tissue loss and gangrene, can have significant implications in patients who have undergone renal transplant and are maintained on immunosuppressive therapy.…”
mentioning
confidence: 99%